Effect of relaxation in salt water on heart rate, blood pressure, and oxygen uptake - Nishimura, M.; Yamamoto, K.; Hoshijma, Y.; Torigoe, Y.; Yamaguchi, H.; Miyachi, M.; Onodera, S. (Biomechanics and Medicine in Swimming VIII, 1999)
The purpose of this study was to clear the cardiovascular response to relaxation in salt water (SW), simple water (W) and out of water (OW) conditions. Two males and four females served as subjects (n=6, mean age: 25.3yrs). Water and room temperature were 30 cC. Heart rate, blood pressure and oxygen uptake were measured during relaxation for each condition. Autonomic nerve activity was estimated with the power spectrum analysis by using the Fast Fourier Transformation (FFf). High (HF; 0.15-0.50 Hz) and low (LF; 0.04-0.15 Hz) frequency areas and the ratio of LF to HF (LFIHF) were calculated as the indices of cardiac parasympathetic nerve activity, sympathetic nerve activity with parasympathetic modulation and sympathetic nerve activity, respectively. There were no significant differences in heart rate, blood pressure and oxygen uptake among the three conditions. Nu (normalized unit ; %) of HF for SW and W were significantly higher than OW. LF/HF for SW and W were significantly lower than OW. These dates suggested that cardiac parasympathetic nerve activity and sympathetic nerve activity during relaxation were affected by immersion.